2020
DOI: 10.1093/cid/ciaa1872
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Diphosphate Concentrations in Dried Blood Spots From Pregnant and Postpartum Adolescent and Young Women Receiving Daily Observed Pre-exposure Prophylaxis in Sub-Saharan Africa

Abstract: Background Intracellular tenofovir diphosphate (TFV-DP) concentration measured in dried blood spots (DBS) is used to monitor cumulative adherence to pre-exposure prophylaxis (PrEP). We evaluated TFV-DP in DBS following daily oral PrEP (emtricitabine 200mg/tenofovir diphosphate 300mg) among pregnant and postpartum adolescent girls and young women (AGYW). Methods Directly observed PrEP was administered for 12 weeks in a pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…There is limited literature on PrEP among this population, but some data suggest that PrEP adherence may be poor, particularly among postpartum women [ 8 , 9 ]. Daily adherence to oral PrEP is important for achieving adequate levels of protection and studies have found that tenofovir levels are lower during pregnancy and/or postpartum compared to non-pregnant or non-lactating women [ 10 , 11 ]. While newer long-acting PrEP drugs such as injectable cabotegravir might alleviate some challenges with adherence, it is likely to be several years before these products are widely available for use among pregnant and breastfeeding women.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited literature on PrEP among this population, but some data suggest that PrEP adherence may be poor, particularly among postpartum women [ 8 , 9 ]. Daily adherence to oral PrEP is important for achieving adequate levels of protection and studies have found that tenofovir levels are lower during pregnancy and/or postpartum compared to non-pregnant or non-lactating women [ 10 , 11 ]. While newer long-acting PrEP drugs such as injectable cabotegravir might alleviate some challenges with adherence, it is likely to be several years before these products are widely available for use among pregnant and breastfeeding women.…”
Section: Introductionmentioning
confidence: 99%
“…While pregnant women have been excluded from clinical trials of PrEP due to unknown effects of FTC/TDF on pregnancy outcomes, the World health organization (WHO) recommends PrEP use among pregnant and breastfeeding women following recent trials and reviews which suggest that PrEP is safe and effective in preventing HIV among this population [18,19]. Despite these successes, continuation in PrEP care and adherence to PrEP remain challenges, especially among pregnant and postpartum women, among whom emerging pharmacokinetic evidence suggests that blood levels of TDF among African AGYW were about one third lower in pregnancy than in postpartum, indicating the need for daily PrEP adherence to maintain effectiveness against HIV infection [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This consideration is essential in pregnant women who require daily dosing for efficacy, given that non-adherence is less forgiving than in postpartum women. (32)…”
Section: Discussionmentioning
confidence: 99%
“…Survey measures were collected at baseline and follow-up visits for all participants (on PrEP and not on PrEP). Survey measures included questions on: (a) basic demographic information and obstetric history (baseline only), (b) partner HIV status, (c) sexual behaviours in the past month and past week (including the number of sex partners, type of sex, frequency of sex and condom use), (d) substance use from the Alcohol Use Disorders Identification Test (AUDIT) (31) and Drug Use Disorders Identification Test (DUDIT) (32), (e) HIV risk perception, (f) intimate partner violence (using the WHO IPV scale (33,34)), (g) perceived partner, community and social support for PrEP, and (h) for PrEP users only, questions related to PrEP adherence according to self-report (seven-day and 30-day recall) and pill count measures, side effects, adverse events, severe adverse events and birth outcomes (after participants have given birth) at follow-up visits.…”
Section: Methodsmentioning
confidence: 99%